[CEU Accreditation]
Recording of the news concerning the registration and accreditation of the CEU in Hungary. The coverage contains interviews with István Teplán (CEU Executive Vice President) and László Mátyás (CEU Academic Pro-Rector) who explain the necessity of the CEU to have not only not only an US accreditation but a Hungarian accreditation as well.